Digitalisasi Museum Cakraningrat sebagai Sumber Literasi Edukasi pada Siswa Di Era Disrupsi 5.0 - Dellia, Prita; Mutiatun, Siti; Amil, Ahmad Jami’ul; Ismail, Nor Hasimah; Narawi, Mohammad Syawal; Pamungkas, Onok Yayang; Hastangka, Hastangka (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Museums are a source of knowledge and literacy for their visitors. However, so far, museum visitors only stop by and don't discuss comprehensive data related to objects seen by visitors. Others create interest in museums by digitizing the objects in them. So this research is a preliminary study before developing barcodes. This research is a preliminary study prior to the development of learning media for literary language and its barcode-based teaching for reading skills to facilitate the learning process in museums and educate local knowledge about relics that are full of information and knowledge. Understanding the contents of the object description utilizes barcode-based technology. The development design used is Research and Development Borg and Gall. There are seven research stages: problems, information collection, product design, product testing, design revision, design validation, and product revision. The barcode application developed can be used on Android phones or the like by utilizing barcodes, while its development is on the use of technology in objects in museums in Cakraningrat Bangkalan Madura of Ajhar Museum. Keywords: Museum, learning resources, reading literacy, barcode application.